Respuesta :

Answer:

(a) Amplitude = 4

(b) [tex]T = \frac{2\pi}{3}[/tex] --- Period

(c)

[tex]C = \frac{\pi}{3}[/tex] --- phase shift

[tex]D =1[/tex] --- vertical shift

Step-by-step explanation:

Given

[tex]f(x) = -4\cos(3x - \pi) + 1[/tex]

Rewrite the function as:

[tex]f(x) = -4\cos(3(x - \frac{\pi}{3}) + 1[/tex]

Solving (a): The amplitude

A cosine function is represented as:

[tex]f(x) = A\cos[B(x - C)] + D[/tex]

Where:

[tex]|A| \to Amplitude[/tex]

So, in this equation (by comparison):

[tex]|A| = |-4|[/tex]

[tex]|A| = 4[/tex]

The amplitude is 4

Solving (b): The period (T)

This is calculated as:

[tex]T = \frac{2\pi}{B}[/tex]

By comparison:

[tex]B =3[/tex]

So:

[tex]T = \frac{2\pi}{3}[/tex]

Solving (c): The shift

The phase shift is C

The vertical shift is D

By comparison:

[tex]C = \frac{\pi}{3}[/tex] --- phase shift

[tex]D =1[/tex] --- vertical shift